Running out of time: exploring women's motivations for social egg freezing - Kylie Baldwin; Lorraine Culley; Nicky Hudson; Helene Mitchell (Taylor & Francis Group, 2019)
Objective: Few qualitative studies have explored women's use of social egg freezing. Derived from an interview study of 31 participants, this article explores the motivations of women using this technology. Methods: Semi-structured interviews were conducted with 31 users of social egg freezing resident in UK (n = 23), USA (n = 7) and Norway (n = 1). Interviews were face to face (n = 16), through Skype and Facetime (n = 9) or by telephone (n = 6). Data were analyzed using interpretive thematic analysis. Results: Women's use of egg freezing was shaped by fears of running out of time to form a conventional family, difficulties in finding a partner and concerns about "panic partnering", together with a desire to avoid future regrets and blame. For some women, use of egg freezing was influenced by recent fertility or health diagnoses as well as critical life events. A fifth of the participants also disclosed an underlying fertility or health issue as affecting their decision. Conclusion: The study provides new insights in to the complex motivations women have for banking eggs. It identifies how women's use of egg freezing was an attempt to "preserve fertility" in the absence of the particular set of "life conditions" they regarded as crucial for pursuing parenthood. It also demonstrates that few women were motivated by a desire to enhance their career and that the boundaries between egg freezing for medical and for social reasons may be more porous than first anticipated.